Pengaruh Pemasangan Kapasitor Daya Terhadap Penghematan Pemakaian Energi Listrik Rumah Tangga. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Electrical energy has become a basic need for modern society. Its flexibility in energy conversion to another form of enery makes people choose this energy. The needs of electrical energy will grow as the increasing of the people prosperity. The use of electrical energy depends on the variety of electrical household products and electronic products that are used regularly. The objectives of this research were to evaluate the effect of power capacitor installation to residential electrical energy saving and to calculate the amount of the energy saving.. The result showed that the installation of power capacitor can save energy. This saving is obtained from decreasing the reactive current that is drawn by the inductive loads. In water pump, refrigeration, AC and others inductive load, power capacitor will give reactive current to these loads, so it increase the power factor, decrease current supply and voltage drop.